IMPLEMENTASI PROGRAM GERAKAN LITERASI SEKOLAH DI SMA: (Studi Evaluasi) - Supadi Supadi; Heru Santoso (Program Studi Manajemen Pendidikan, 2021)
This study is a study of the evaluation of gaps in the implementation of the School Literacy Movement program in two high school in the South Jakarta area. As an intervention program launched by the government to assist learners in developing critical, creative, innovative, entrepreneurial attitudes, social empathy behavior, and love for knowledge, it is necessary to know the extent to which the program has an impact in improving reading skills understanding in learners and what gaps in running GLS programs through the gap evaluation model (The Discrepancy Evaluation Model). The model developed by Malcolm Provus with this qualitative approach generally aims to obtain information about gaps in the implementation of the GLS program. Research data is obtained through observations, interviews, and document studies. Data analysis is carried out with three flow of activities that occur simultaneously, namely: data reduction, data presentation, data withdrawal or verification. results showed that the positive impact of gls program implementation can be monitored even though academic measurement has not been done. One of the related to the success of KBM is the increased readiness of students in attending KBM, increased confidence when speaking in public and writing. Gaps in program implementation in both high schools appear in the design of the target and installation of the program implementation, although both boil to the development of language skills and literacy of learners. In addition, there needs to be a firmer emphasis in the master design that the establishment of a literate environment is the responsibility of all school residents. Despite the gaps that occur in the implementation of school conditions have allowed the formation of a literate environment.